Synergistic therapeutic approach for hemorrhoids: integrating mesenchymal stem cells with diosmin-hesperidin to target tissue edema and inflammation - M. Hidayat Budi Kusumo; Adi Prayitno; Soetrisno .; Abdurahman Laqif (Archives of Medical Science)
Introduction Mesenchymal stem cells (MSCs) have promising regenerative properties in tissue repair and anti-inflammatory responses. This study aimed to investigate the effects of MSCs and their combination with micronized purified flavonoid fraction (MPFF) in a croton oil-induced hemorrhoids model on tissue edema, inflammation, and underlying molecular mechanisms.